Mobile phone security notification application in symbian operating system environment / Mohamad Izham Liman - Liman, Mohamad Izham (2010)
Nowadays, the security is important to protect our information or our device. Mobile phone is a technology of electronic device which is small in size but has a lot of capabilities. Nowadays, almost everyone in this world can afford to buy at least one mobile phone. Mobile phone as we all know have store the information and many data and important as a personal computer which is to enable people to access their data or work at anytime and anywhere. The prototype application that will be developed is the Mobile Phone Security Notification Application. This prototype is created mainly for the user that uses Symbian Operating System via Nokia mobile phone. This prototype application is develop on a mobile platform. The Rapid Application Development (RAD) is used as development model in developing this project. The application is develop by using Carbide.C-H-1.3 and using C++programming language. The main architecture behind the development of the mobile security notification is the function to send SMS notification. In addition, hope that this prototype application can contribute further information regarding a dynamic development of security notification on mobile platform.